(3EQTGO GdbGUO Edi CSfi GdebGUOs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s
(3ChdgG (B:s
(3eGPG jSJajOg efg ajchf Ydi HUjQI ef CeQg s
(3BNQgG (B:s
(3hdjcf gPG AGNQ GdcdGe ai gPg GdQSGdI fLRJ GdQSGdI GdeHGQcI HMeO Gddg hYhfg hGdUdGI hGdSdGe Ydi SjOfG eMeO QShd Gddg hYdi Bdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B66s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs